Recent Progresses in Development of Biosensors for Thrombin Detection - Reza Eivazzadeh-Keihan; Zahra Saadatidizaji; Ali Maleki; Miguel de la Guardia; Mohammad Mahdavi; Sajjad Barzegar; Samad Ahadian (Biosensors, 2022)
Thrombin is a serine protease with an essential role in homeostasis and blood coagulation. During vascular injuries, thrombin is generated from prothrombin, a plasma protein, to polymerize fibrinogen molecules into fibrin filaments. Moreover, thrombin is a potent stimulant for platelet activation, which causes blood clots to prevent bleeding. The rapid and sensitive detection of thrombin is important in biological analysis and clinical diagnosis. Hence, various biosensors for thrombin measurement have been developed. Biosensors are devices that produce a quantifiable signal from biological interactions in proportion to the concentration of a target analyte. An aptasensor is a biosensor in which a DNA or RNA aptamer has been used as a biological recognition element and can identify target molecules with a high degree of sensitivity and affinity. Designed biosensors could provide effective methods for the highly selective and specific detection of thrombin. This review has attempted to provide an update of the various biosensors proposed in the literature, which have been designed for thrombin detection. According to their various transducers, the constructions and compositions, the performance, benefits, and restrictions of each are summarized and compared.